Circular pathways in construction: environmental life cycle assessment of bio-based fiber-reinforced building component - Baltrocchi, Alberto Pietro Damiano; Shafique, Muhammad (Frontiers in Sustainability, 2026)
The construction sector is one of the most significant contributors to global environmental impacts, particularly due to its high material and energy demands. Developing sustainable alternatives to conventional building materials is, therefore, a critical step toward reducing the environmental impact of this sector. The integration of recycled bio-based fibers with traditional reinforcement is proposed as an alternative solution to mitigate environmental impacts. This study evaluated the environmental benefits of replacing traditional steel reinforcement with recycled bio-based hemp and bamboo fibers in a reinforced concrete beam using the Life Cycle Assessment (LCA) methodology, excluding the evaluation of the mechanical performance of the replacement materials from its scope. The results show that, overall, replacing steel has significant benefits for several impact categories even at low replacement rates for the reinforced concrete beam. For instance, in terms of global warming potential (GW), the emissions decrease from 362 kg CO2 eq for beam for the steel-reinforced concrete to 324 kg CO2 eq for beam for 30% steel replacement with recycled hemp and 312 kg CO2 eq for beam for 30% steel replacement with recycled bamboo fiber. Therefore, the GW emissions decrease by around 14% for the reinforced concrete beam. This study contributes to the scientific literature by providing concrete data on the benefits of using bio-based recycled fibers even at low replacement rates. This research suggests that utilizing recycled bio-based materials could be a practical approach to enhancing the sustainability of construction materials from a circular economy perspective.